Registration of Seven Upland Cotton Germplasm Lines (PSLC‐U01, PSLC‐U02, PSLC‐U03, PSLC‐U04, PSLC‐U05, PSLC‐U06, and PSLC‐U07) for the Texas High Plains Possessing Superior Fiber Traits and Good Yield. Issue 1 (29th November 2018) - Burke, John J.; Ulloa, Mauricio
Abstract : Seven upland cotton ( Gossypium hirsutum L.) germplasm lines—PSLC‐U01 (Reg. No. GP‐1038, PI 687031), PSLC‐U02 (Reg. No. GP‐1039, PI 687032), PSLC‐U03 (Reg. No. GP‐1040, PI 687033), PSLC‐U04 (Reg. No. GP‐1041, PI 687034), PSLC‐U05 (Reg. No. GP‐1042, PI 687035), PSLC‐U06 (Reg. No. GP‐1043, PI 687036), and PSLC‐U07 (Reg. No. GP‐1044, PI 687037)—were developed by the USDA–ARS and jointly released with Cotton Incorporated in 2017. The plant stress laboratory cotton (PSLC) germplasm lines originated from the cross of two distinct commercial cultivars from different cotton growing regions of the United States, 'Phytogen 72' (PHY 72 [female] far west [PVP #200100115]) and 'Stoneville 474' (STV 474 [male] mid‐south [PVP# 9400152]). The PSLC‐U01 to PSLC‐U07 lines were originally selected from a total of 137 F7 recombinant inbred lines in 2014; each line derived from a single seed or plant decent (F1:7 ). In 2014 and 2016, at the USDA–ARS Plant Stress and Germplasm Development Research Unit, Lubbock, TX, 137 and 27 lines were evaluated in a randomized complete block design with three and four single 6.1‐m‐plot replications under two irrigation regimes (regular and reduced by half using subsurface drip irrigation system), respectively. In 2016, 7 lines of the 27 advanced breeding lines (PSLC‐U01, PSLC‐U02, PSLC‐U03, PSLC‐U04, PSLC‐U05, PSLC‐U06, and PSLC‐U07) were selected for release on the basis of good overall agronomic performance and superior fiber quality properties in these tests when they were compared with original parents and four upland commercial check cultivars.